DESIGNING OF WOMEN’S CLOTHING COLLECTIONS WITH PERFORATION - Пашкевич, К. Л.; Креденець, Н. Д.; Постельняк, А. В.; Кінчина, О. М. (Art and Design, 2018)
Determination of features design features of the creative collection of women’s clothing using decorative finishes – perforations. The complex approach of the system-structural method and the morphological analysis of the initial object of the investigation with its subsequent synthesis on the basis of the obtained data is applied. The analysis of the design of clothing collections with various types of modern finishes is carried out, collections of modern Ukrainian and foreign designers are analyzed with the purpose of determining modern methods of production of perforation in clothes and modern fashion trends. The drawings for perforation in clothes and ways of its combination with other types of decoration of the clothing surface are considered. A classification of the types of perforations and methods of its production has been developed, on the basis of which an actual collection of women’s clothing with manual perforation has been developed.